RNase III coding genes modulate the cross-kingdom biofilm of Streptococcus mutans and Candida albicans - Lu, Yangyu; Lei, Lei; Deng, Yalan; Zhang, Hongyu; Xia, Mengying; Wei, Xi; Yang, Yingming; Hu, Tao (Frontiers in Microbiology, 2022)
Streptococcus mutans constantly coexists with Candida albicans in plaque biofilms of early childhood caries (ECC). The progression of ECC can be influenced by the interactions between S. mutans and C. albicans through exopolysaccharides (EPS). Our previous studies have shown that rnc, the gene encoding ribonuclease III (RNase III), is implicated in the cariogenicity of S. mutans by regulating EPS metabolism. The DCR1 gene in C. albicans encodes the sole functional RNase III and is capable of producing non-coding RNAs. However, whether rnc or DCR1 can regulate the structure or cariogenic virulence of the cross-kingdom biofilm of S. mutans and C. albicans is not yet well understood. By using gene disruption or overexpression assays, this study aims to investigate the roles of rnc and DCR1 in modulating the biological characteristics of dual-species biofilms of S. mutans and C. albicans and to reveal the molecular mechanism of regulation. The morphology, biomass, EPS content, and lactic acid production of the dual-species biofilm were assessed. Quantitative real-time polymerase chain reaction (qRT-PCR) and transcriptomic profiling were performed to unravel the alteration of C. albicans virulence. We found that both rnc and DCR1 could regulate the biological traits of cross-kingdom biofilms. The rnc gene prominently contributed to the formation of dual-species biofilms by positively modulating the extracellular polysaccharide synthesis, leading to increased biomass, biofilm roughness, and acid production. Changes in the microecological system probably impacted the virulence as well as polysaccharide or pyruvate metabolism pathways of C. albicans, which facilitated the assembly of a cariogenic cross-kingdom biofilm and the generation of an augmented acidic milieu. These results may provide an avenue for exploring new targets for the effective prevention and treatment of ECC.